The Role of Emotional Intelligence (Emotional Quotient/EQ) in Shaping Students’ Personality From the Perspective of Educational Psychology - Kalsum, Umi; Sirozi, Muhammad (FKIP - Universitas Riau, 2025)
This study aims to analyse the role of emotional intelligence (EQ) in shaping students’ personalities through a literature review approach. Emotional intelligence refers to the ability to recognise, understand, manage, and direct emotions effectively, both in oneself and in others. This competence has significant implications for the development of students’ character and social adjustment. Using a qualitative literature study method, this research examines relevant theories and findings from previous studies on emotional intelligence and personality formation. It integrates the perspectives of Salovey and Mayer, Daniel Goleman, Reuven Bar-On, Howard Gardner, Sigmund Freud, Gordon Allport, Carl Rogers, and Erik Erikson. The analysis reveals that emotional intelligence significantly contributes to the development of a stable, adaptive, and positive personality. Core dimensions influencing this process include self-awareness, self-regulation, empathy, motivation, and social skills. Personality theories by Freud, Allport, Rogers, and Erikson support the notion that emotional regulation is essential for identity formation, integrity, and healthy social relations. Therefore, this study highlights the importance of educational strategies that integrate intellectual and emotional growth within family and school environments to foster balanced, resilient, and morally grounded student personalities.